2019
DOI: 10.1002/qj.3664
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deepening and mesoscale organization of shallow convection on stratiform cloudiness in the downstream trades

Abstract: In this study we use large‐eddy simulation to explore the factors controlling stratiform cloudiness in the downstream trades. We perform sensitivity experiments with different large‐scale forcings, radiation specifications and domain sizes, which isolate the influence of convective deepening, moisture–radiation interactions and mesoscale organization, respectively. Across the simulations with different large‐scale forcings, we find that the deepening of the cloud layer and the associated increase in precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 36 publications
7
23
0
Order By: Relevance
“…Hohenegger et al (2019) find similar dependencies of cloud fraction on grid spacing between 2.5 km and 80 km and hypothesize that if horizontal resolution is not sufficient for proper mixing, the boundary layer grows and clouds form higher at colder temperatures leading also to more cloudiness. The decrease in cloud fraction between the simulations with 600 m and 300 m grid spacing is still substantial and not converged, which is in agreement with idealized modelling studies showing that LEM underestimates cloud fraction when the grid spacing becomes as fine as 50 m (Vogel et al, 2019).…”
Section: Vertical Distribution Of Water Vapor and Cloud Fractionsupporting
confidence: 81%
See 1 more Smart Citation
“…Hohenegger et al (2019) find similar dependencies of cloud fraction on grid spacing between 2.5 km and 80 km and hypothesize that if horizontal resolution is not sufficient for proper mixing, the boundary layer grows and clouds form higher at colder temperatures leading also to more cloudiness. The decrease in cloud fraction between the simulations with 600 m and 300 m grid spacing is still substantial and not converged, which is in agreement with idealized modelling studies showing that LEM underestimates cloud fraction when the grid spacing becomes as fine as 50 m (Vogel et al, 2019).…”
Section: Vertical Distribution Of Water Vapor and Cloud Fractionsupporting
confidence: 81%
“…December 2013 is a stronger secondary maximum of cloud fraction near 2 km height in the simulations with 600 m to 2.5 km grid spacing. These small stratiform cloud shields below the inversion are often present in both model and observations (Lamer et al, 2015;Vogel et al, 2019) but cannot be found in the WALES data in our time period. The LEM simulations with finest grid spacing (300 m) are closer to the observations in this case.…”
Section: Vertical Distribution Of Water Vapor and Cloud Fractionmentioning
confidence: 56%
“…The rate at which cloudiness reduces with increasing mixing depends both on the shallowness of the present-day cloud profile (Brient et al 2016), and on the coupling between convective mixing, surface turbulent fluxes and low-cloud radiative effects (Vial et al 2016). In contrast to climate models, cloud-base cloudiness in large-eddy simulations (LES) and in observations is much less sensitive to changes in the large-scale environment (Bretherton et al 2013;Blossey et al 2013;Vogel et al 2016;Nuijens et al 2014Nuijens et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…outside deep convective regions (e.g., Muller and Held, 2012;Hohenegger and Stevens, 2016;Wing et al, 2017).…”
Section: Vertical Distribution Of Water Vapor and Cloud Fractionmentioning
confidence: 99%